2007
DOI: 10.1002/pssc.200674729
|View full text |Cite
|
Sign up to set email alerts
|

Realization of AlGaN/GaN HEMTs on Si‐on‐polySiC substrates

Abstract: AlGaN/GaN High Electron Mobility Transistors have been realized on resistive Si(111)/SiO2/polySiC substrates. The epitaxial structures were grown by Molecular Beam Epitaxy. The structural, optical, and electrical properties of these films are studied and compared with those of reference heterostructures grown on thick Si(111) substrates. Channel mobility of 1470 cm2/Vs at room temperature and sheet carrier density of 6.65x1012 cm–2 have been achieved. Field effect transistors with 3.6 µm x 100 µm gates have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Such a material is SiC, firstly employed by Takeuchi and Davis . Later, micrometer thick 3C‐SiC(111) layers were used for the same purpose . Albeit, it was shown that for reliable heteroepitaxial growth and device fabrication thick silicon carbide layers are not necessary .…”
Section: Introductionmentioning
confidence: 99%
“…Such a material is SiC, firstly employed by Takeuchi and Davis . Later, micrometer thick 3C‐SiC(111) layers were used for the same purpose . Albeit, it was shown that for reliable heteroepitaxial growth and device fabrication thick silicon carbide layers are not necessary .…”
Section: Introductionmentioning
confidence: 99%